Addressing biopiracy through the BBNJ agreement's marine genetic resources framework: Reflections from the clarion-clipperton zone for Indonesia’s future - Nasywa Intan Ramadhanty (Priviet Social Sciences Journal, 2026)
Marine Genetic Resources (MGRs) located in Areas Beyond National Jurisdiction (ABNJ) have long been subject to asymmetric appropriation, with a single corporation controlling 47% of patented marine genetic sequences and entities from just ten countries holding 98% of such patents (Blasiak et al., 2018). This article examines how the United Nations Convention on the Law of the Sea (UNCLOS) 1982 facilitates this appropriation through structural legal gaps, how the BBNJ Agreement (2023) addresses them, and the implications for Indonesia. Employing a normative juridical methodology with statutory and conceptual approaches, the study finds that the UNCLOS definition of "resources" excludes MGRs from the Common Heritage of Mankind regime, while Parts XIII–XIV provide no binding benefit-sharing mechanism. These conditions are empirically observable in the Clarion-Clipperton Zone (Rabone et al., 2023). Part II of the BBNJ Agreement (2023) introduces a dedicated MGR framework comprising notification obligations, a Standardized Batch Identifier, and two-phase benefit-sharing; however, four structural limitations persist: retroactivity opt-out, deferred monetary benefit-sharing, derivatives ambiguity, and an unresolved ISA interface (Bodansky, 2024; Humphries, 2025). For Indonesia, capturing the Agreement's opportunities in data access, Special Fund support, and COP participation requires regulatory consolidation across fragmented domestic instruments, a designated national focal point, and strategic investment in deep-sea research capacity.